ASSESSMENT OF THE CLINICAL EFFICACY AND SAFETY OF LONG-PULSED NEODYMIUM (1064-NM) LASER THERAPY VERSUS STANDARD MEDICAL THERAPY IN MODERATE ACNE VULGARIS - Qoqazy, Belal A. S.; Melekhovets, Oksana K. (Eastern Ukrainian Medical Journal, 2025)
Introduction. Moderate acne vulgaris represents a long-standing inflammatory condition of the pilosebaceous unit, in which visible lesions on the face and trunk markedly impair self-image and emotional well-being. Conventional combined medical therapy is widely used but often shows slow onset of action, long treatment duration, and adverse effects, which reduces patient adherence. These limitations have stimulated interest in non-pharmacological approaches. Long-Pulsed Neodymium (1064-nm) Laser Therapy offers targeted photothermal effects on sebaceous structures and inflammatory pathways with minimal downtime. Aim. To evaluate the anti-inflammatory effect, clinical improvement, patient satisfaction, overall tolerability, and the potential reduction of treatment-related adverse effects achieved with long-pulsed 1064-nm neodymium laser therapy compared with Standard Medical Therapy in moderate acne vulgaris. Materials and Methods. This prospective randomized clinical trial included 80 adults aged 18–40 years diagnosed with moderate acne vulgaris. Participants were evenly allocated into two study arms (n = 40 per group; 15 males and 25 females). Group 1 (Standard Medical Therapy) received a guideline-based regimen consisting of nightly topical benzoyl peroxide (5%–10%) combined with adapalene (0.1%–0.3%), as well as oral doxycycline administered within standard therapeutic limits (100–200 mg/day). All medication choices and dosages adhered to contemporary evidence-based recommendations for moderate acne management. Group 2 (Laser therapy) underwent six treatment sessions delivered at two-week intervals using a long-pulse 1064-nm Nd:YAG laser. The procedure employed clinically appropriate low-to-moderate fluence, an intermediate pulse duration, and a medium spot size, in line with established non-ablative acne treatment protocols. Dynamic epidermal cooling and individualized energy adjustments were implemented to ensure both patient safety and optimal therapeutic effect. Clinical severity was evaluated using the Global Acne Grading Scale (GAGS) at baseline, week 6, and week 12. Satisfaction levels were documented using a numerical visual analogue rating scale ranging from 0 to 10, and all local skin reactions were systematically recorded throughout the study period. Results. Baseline characteristics showed no significant differences (p = 0.87). Both groups improved by week 6 (p<0.05), with a more pronounced reduction in GAGS scores in the laser group (p = 0.035). By week 12, mean GAGS scores were lower with laser therapy (11.8 ± 2.5) than with medical therapy (14.6 ± 2.8; p = 0.007). VAS satisfaction scores were higher in the laser group (8.3 ± 0.8 vs. 6.7 ± 0.9; p = 0.004).Adverse effects were mild: transient erythema (12.5%) and slight edema (10%) resolved within 48 hours. Medical therapy caused dryness (20%) and irritation (17.5%). No pigment changes or scarring occurred in either group. Conclusion. Long-pulse 1064-nm Nd:YAG laser therapy provided stronger clinical improvement, higher patient satisfaction, and fewer persistent adverse effects compared with combined topical–systemic therapy. It represents an effective, well-tolerated option for moderate acne.